2007
DOI: 10.1097/mao.0b013e318067bd24
|View full text |Cite
|
Sign up to set email alerts
|

1-Year Postactivation Results for Sequentially Implanted Bilateral Cochlear Implant Users

Abstract: Bilateral cochlear implantation allowed for better speech recognition in noise relative to unilateral performance for a group of 12 children who underwent sequential bilateral cochlear implantation at various ages. There was not a statistically significant relationship between speech recognition in noise benefit, which was defined as the difference in performance between the first implanted ear and the bilateral condition and the age at which the second implant was received. Children receiving bilateral cochle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 26 publications
6
32
2
Order By: Relevance
“…The median squelch effect for both CI 1 and CI 2 (0 dB and 1 dB, respectively) was within the accepted range of ≤2 dB (Laszig et al, 2004;Litovsky et al, 2006;Van Deun et al, 2010) on a 5% level of significance. The median summation benefits for both CI 1 (0 dB) and CI 2 (2 dB) added to BiCI in the NF condition was within the accepted value range of ≤6 dB (Litovsky et al, 2006;Wolfe et al, 2007;Eapen, Buss, Adunka, Pillsbury & Buchman, 2009;Van Deun et al, 2010) at the 5% level of significance. The median SRM benefit values were within the accepted range of 0 to 4 dB (Litovsky et al, 2006;Van Deun et al, 2010) only when the noise was directed to CI 1 at the 5% level of significance.…”
Section: Bilateral Spatial Benefitssupporting
confidence: 51%
See 1 more Smart Citation
“…The median squelch effect for both CI 1 and CI 2 (0 dB and 1 dB, respectively) was within the accepted range of ≤2 dB (Laszig et al, 2004;Litovsky et al, 2006;Van Deun et al, 2010) on a 5% level of significance. The median summation benefits for both CI 1 (0 dB) and CI 2 (2 dB) added to BiCI in the NF condition was within the accepted value range of ≤6 dB (Litovsky et al, 2006;Wolfe et al, 2007;Eapen, Buss, Adunka, Pillsbury & Buchman, 2009;Van Deun et al, 2010) at the 5% level of significance. The median SRM benefit values were within the accepted range of 0 to 4 dB (Litovsky et al, 2006;Van Deun et al, 2010) only when the noise was directed to CI 1 at the 5% level of significance.…”
Section: Bilateral Spatial Benefitssupporting
confidence: 51%
“…The latter can improve speech perception scores up to 19% in quiet and up to 16% in noise . Summation effects previously reported vary in effect sizes of up to 6 dB in some users and no effect or negative effects in others Laszig et al, 2004;Litovsky et al, 2006;Wolfe et al, 2007). The squelch effect is another possible advantage of bilateral hearing through bilateral cochlear implantation.…”
mentioning
confidence: 87%
“…As with outcomes for children with unilateral cochlear implants, the degree of improvement varies widely between individuals. Improved speech perception in noise has been associated with shorter periods of hearing loss in the second ear in some studies (Litovsky et al, 2004;Peters et al, 2007;Steffens et al, 2008), but not all have found this link (Kuhn-Inacker et al, 2004;Litovsky et al, 2006a;Wolfe et al, 2007). Two studies that did not find improvements in speech perception in noise included children who had a long time period between their first and second cochlear implants.…”
Section: Speech Perceptionmentioning
confidence: 99%
“…There appears to be a consensus that children receiving a second implant over the age of 4 years perform much more poorly on speech recognition and sound localization tasks, and do not show evidence of true binaural processing (for example, Galvin et al, 2007a;Johnston et al, 2009;Wolfe et al, 2007). Current evidence suggests that simultaneous bilateral implantation is a safe surgical procedure, and may also offer advantages to ease of adaptation, although there may be greater challenges associated with programming and managing two devices in younger children (Ramsden et al, 2009).…”
Section: Timing Of First and Second Cochlear Implants; Sequential Andmentioning
confidence: 99%
See 1 more Smart Citation